High-Fat Diet Induces Resistance to Ghrelin and LEAP2 Peptide Analogs in Mice - Holá, L; Tureckiuová, T; Kuneš, Jiří; Železná, Blanka; Maletínská, Lenka (Physiological research, 2023)
Recent data suggest that the orexigenic peptide ghrelin and liver-expressed antimicrobial peptide 2 (LEAP2) have opposing effects on food intake regulation. Although circulating ghrelin is decreased in obesity, peripheral ghrelin administration does not induce food intake in obese mice. Limited information is available on ghrelin resistance in relation to LEAP2. In this study, the interplay between ghrelin and LEAP2 in obesity induced by a high-fat (HF) diet in mice was studied. First, the progression of obesity and intolerance to glucose together with plasma levels of active and total ghrelin, leptin, as well as liver LEAP2 mRNA expression at different time points of HF diet feeding was examined. In addition, the impact of switch from a HF diet to a standard diet on plasma ghrelin and LEAP2 production was studied. Second, sensitivity to the stable ghrelin analogue [Dpr3]Ghrelin or our novel LEAP2 analogue palm-LEAP2(1-14) during the progression of HF diet-induced obesity and after the switch for standard diet was investigated. Food intake was monitored after acute subcutaneous administration. HF diet feeding decreased both active and total plasma ghrelin and increased liver LEAP2 mRNA expression along with intolerance to glucose and the switch to a standard diet normalized liver LEAP2 mRNA expression and plasma level of active ghrelin, but not of total ghrelin. Additionally, our study demonstrates that a HF diet causes resistance to [Dpr3]Ghrelin, reversible by switch to St diet, followed by resistance to palm-LEAP2(1-14). Further studies are needed to determine the long-term effects of LEAP2 analogues on obesity-related ghrelin resistance.
Keywords: dieta s vysokým obsahem tuků; receptory ghrelinu; Animals; Receptors, Ghrelin; RNA, Messenger; messenger RNA; ghrelin; Ghrelin; Diet, High-Fat; Mice; Glucose; Obesity; glukosa; myši; obezita; zvířata